Resource allocation for wireless networks basics, techniques, and applications - Han, Zhu 1974- (Cambridge University Press, 2008)
Do you need to improve wireless system performance? Learn how to maximise the efficient use of resources with this systematic and authoritative account of wireless resource management. Basic concepts, optimization tools and techniques, and application examples, are thoroughly described and analysed, providing a unified framework for cross-layer optimization of wireless networks. State-of-the-art research topics and emerging applications, including dynamic resource allocation, cooperative networks, ad hoc/personal area networks, UWB, and antenna array processing, are examined in depth. If you are involved in the design and development of wireless networks, as a researcher, graduate student or professional engineer, this is a must-have guide to getting the best possible performance from your network.